Lifespan Development. - Anthis, Kristine (2007)
Keywords: dept.psy; faculty_collection; sabbatical_report

EdPsych Modules. - Durwin, Cheryl C. (2007)
Keywords: dept.psy; faculty_collection; sabbatical_report

Re-Examining the Long-Term Effects of Experiencing Parental Death in Childhood on Adult Psychopathology. - Jacobs, John R. (2006)
Keywords: dept.psy; faculty_collection

Learning and Behavior. - Mazur, James E. (2004)
Keywords: dept.psy; faculty_collection; sabbatical_report

Resource Manual for Psychology and Law. - Tolchin, Gerald (Fall;Psychology., 2000)
Keywords: dept.psy; faculty_collection; sabbatical_report

Mrs. Job - Affinito, Mona Gustafson (iUniverse Inc, 2009)
"Beautiful, feisty Dara, rising from nomad to princess, experiences joy, spiritual and marital conflict, and unspeakable trials, without surrendering her love for Job and for her best friend Adah"--p. 4 of Cover.
Keywords: Christianity; Fiction; Religious fiction, American; Fiction; Suffering; Fiction; Wives; Job (Biblical figure); Religious aspects; dept.psy; faculty_collection

Forgiving One Page at a Time: The Diary of Your Journey to Restoration and Confidence - Affinito, Mona Gustafson (AuthorHouse, 2007)
Keywords: Forgiveness; dept.psy; faculty_collection

Learning and Behavior - Mazur, James E. (Pearson/Prentice Hall, 2006)
Keywords: Learning, Psychology of; Textbooks; Textbooks; Behavior modification; Textbooks; Conditioned response; Textbooks; Psychology, Comparative; dept.psy; faculty_collection

Sabbatical Leave Report - Sherman, William M. (2005)
Sabbatical leave report outlining time spent revising the textbook, "Behavior modification", conducting a research project entitled "Motherhood ideology, role balance, and health-promoting behaviors of non-tenured academic mothers with preschool children", and working on course proposals for the Department of Psychology.
Keywords: dept.psy; faculty_collection; sabbatical_report

The Roles of Vasopressin and Oxytocin in Memory Processing - McEwen, Barbara B. (Advances in pharmacology ; v. 50, 2004)
Keywords: Physiological aspects; Research; Memory; Research; Neuropeptides; Research; Oxytocin; Vasopressin; dept.psy; faculty_collection

Emergence of Uncertainty: A Microgenetic Study of the Preschool Period, Sabbatical Leave Report - Kahlbaugh, Patricia (2003)
Keywords: dept.psy; faculty_collection; sabbatical_report

Multiple Independent Identification Decisions: A Method of Calibrating Eyewitness Identifications - Pryke, S.; Lindsay, R.C.L.; Dysart, J.E.; Dupuis, P. (Journal of Applied Psychology, 2004)
Two experiments (N = 147 and N = 90) explored the use of multiple independent lineups to identify a target seen live. In Experiment 1, simultaneous face, body, and sequential voice lineups were used. In Experiment 2, sequential face, body, voice, and clothing lineups were used. Both studies demonstrated that multiple identifications (by the same witness) from independent lineups of different features are highly diagnostic of suspect guilt (G. L. Wells & R. C. L. Lindsay, 1980). The number of suspect and foil selections from multiple independent lineups provides a powerful method of calibrating the accuracy of eyewitness identification. Implications for use of current methods are discussed.
Keywords: Decision Making; Humans; Recognition (Psychology); Visual Perception; article; decision making; dept.psy; human; recognition; vision

Possible selves in the lives of adult women: A short-term longitudinal study - Anthis, K. (Possible Selves: Theory, Res. and Appl., 2006)
The current study examined the number and content of possible selves in the lives of adult women over the course of a five-month interval. Based on previous empirical studies of possible selves, a variety of hypotheses were proposed that addressed cohort differences in possible selves, continuity and change in possible selves, and predicting changes in possible selves over time with ego-identity. The results indicated mixed support for the hypotheses, but basically replicated previous research findings on possible selves. The findings are discussed in terms of how they extend both descriptive and predictive knowledge of possible selves. © 2006 by Nova Science Publishers, Inc. All rights reserved.
Keywords: dept.psy

The test of malingered incompetence (TOMI): A forced-choice instrument for assessing cognitive malingering in competence to stand trial evaluations - Colwell, K.; Colwell, L.H.; Perry, A.T.; Wasieleski, D.; Billings, T. (American Journal of Forensic Psychology, 2008)
The TOMI consists of two 25-item, two-alternative, forced-choice scales - General Knowledge (TOMI-G) and Legal Knowledge (TOMI- L) - designed to detect malingered cognitive impairment in CST evaluations. The TOMI was derived and validated with a university sample (N = 242), with a cut score of < 21 providing maximum classification accuracy of hon est and dishonest respondents. Subsequently, the TOMI was administered to forensic inpatient residents (N = 30) and was compared to existing, well- established tests of malingering (the Rey-FIT and the TOMM). Results indi cated strong correlations and predictive agreement for both scales, and dis tinction between honest and probable dishonest respondents for the TOMI-L. A third study provided additional validation for the TOMI in distinguishing honest from dishonest student respondents (N = 120) and examined the ef fects of motivation on response style. For dishonest responders, those in the high motivation group scored significantly lower than those in the low moti vation group, further betraying their dishonesty. The utility of the TOMI as a useful, novel tool for forensic practitioners is discussed. Copyright 2008 American Journal of Forensic Psychology.
Keywords: adult; article; clinical evaluation; cognitive defect; controlled study; dept.psy; diagnostic and statistical manual of mental disorders; female; forced choice method; human; major clinical study; male; malingering; mental disease; mental performance; mental test; psychologic assessment; ⛔ No DOI found

The Tragedy of Child Care in America - Zigler, Edward; Marsland, Katherine W.; Lord, Heather (Yale University Press, 2009)
Why the United States has failed to establish a comprehensive high-quality child care program is the question at the center of this book. Edward Zigler has been intimately involved in this issue since the 1970s, and here he presents a firsthand history of the policy making and politics surrounding this important debate. Good-quality child care supports cognitive, social, and emotional development, school readiness, and academic achievement. This book examines the history of child care policy since 1969, including the inside story of America's one great attempt to create a comprehensive system of child care, its failure, and the lack of subsequent progress. Identifying specific issues that persist today, Zigler and his coauthors conclude with an agenda designed to lead us successfully toward quality care for America's children. © 2009 by Yale University. All rights reserved.
Keywords: Child care; Government policy; Services for; United States; United States; Child welfare; United States; Children; dept.psy; faculty_collection

The predictive validity of the Five-Factor Model of personality with preschool age children: A nine year follow-up study☆ - Abe, Jo Ann A (Journal of Research in Personality, 2005)
This study examined whether maternal ratings of the Five-Factor Model (FFM) obtained when children were 3.5 years would show theoretically coherent patterns of relations with a variety of behavioral referents in the laboratory at 5 years as well as with maternal and self-ratings of psychological functioning in adolescence. As expected, Agreeableness and Conscientiousness were associated with measures of self-regulation at both ages as well as with an internal locus of control, but only Conscientiousness was associated with high academic performance. By contrast, Neuroticism was associated with measures of anxiety and Extraversion was associated with difficulty inhibiting behaviors at both ages. Openness to Experience was associated with sophisticated play behavior at 5 years and self-confidence in adolescence. Overall, this study yielded strong support for the predictive validity of the FFM with preschool age children and provided further evidence that there are striking continuities in personality from early childhood to adolescence. (c) 2004 Elsevier Inc. All rights reserved.
Keywords: dept.psy; peer-reviewed

Use of visual information in speech perception: evidence for a visual rate effect both with and without a McGurk effect. - Brancazio, Lawrence; Miller, Joanne L (Perception & psychophysics, 2005)
The McGurk effect, where an incongruent visual syllable influences identification of an auditory syllable, does not always occur, suggesting that perceivers sometimes fail to use relevant visual phonetic information. We tested whether another visual phonetic effect, which involves the influence of visual speaking rate on perceived voicing (Green & Miller, 1985), would occur in instances when the McGurk effect does not. In Experiment 1, we established this visual rate effect using auditory and visual stimuli matching in place of articulation, finding a shift in the voicing boundary along an auditory voice-onset-time continuum with fast versus slow visual speech tokens. In Experiment 2, we used auditory and visual stimuli differing in place of articulation and found a shift in the voicing boundary due to visual rate when the McGurk effect occurred and, more critically, when it did not. The latter finding indicates that phonetically relevant visual information is used in speech perception even when the McGurk effect does not occur, suggesting that the incidence of the McGurk effect underestimates the extent of audio-visual integration.
Keywords: *Speech Perception; *Visual Perception; Adolescent; Adult; Auditory Perception; Cues; Humans; Middle Aged; dept.psy

Effects of reinforcer probability, delay, and response requirements on the choices of rats and pigeons: Possible species differences - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2005)
In Experiment 1 with rats, a left lever press led to a 5-s delay and then a possible reinforcer. A right lever press led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials to estimate an indifference point, or a delay at which the two alternatives were chosen about equally often. Indifference points increased as the probability of reinforcement for the left lever decreased. In some conditions with a 20% chance of food, a light above the left lever was lit during the 5-s delay on all trials, but in other conditions, the light was only lit on those trials that ended with food. Unlike previous results with pigeons, the presence or absence of the delay light on no-food trials had no effect on the rats' indifference points. In other conditions, the rats showed less preference for the 20% alternative when the time between trials was longer. In Experiment 2 with rats, fixed-interval schedules were used instead of simple delays, and the presence or absence of the fixed-interval requirement on no-food trials had no effect on the indifference points. In Experiment 3 with rats and Experiment 4 with pigeons, the animals chose between a fixed-ratio 8 schedule that led to food on 33% of the trials and an adjusting-ratio schedule with food on 100% of the trials. Surprisingly, the rats showed less preference for the 33% alternative in conditions in which the ratio requirement was omitted on no-food trials. For the pigeons, the presence or absence of the ratio requirement on no-food trials had little effect. The results suggest that there may be differences between rats and pigeons in how they respond in choice situations involving delayed and probabilistic reinforcers.
Keywords: *Behavior, Animal/ph [Physiology]; *Choice Behavior; *Reaction Time; *Reinforcement, Psychology; Animals; Behavior, Animal; Choice; Choice Behavior; Columbidae; Delay; Fixed interval; Fixed ratio; Key peck; Lever press; Male; Pigeons; Probability; Rats; Rats, Sprague-Dawley; Reaction Time; Reinforcement (Psychology); Species Specificity; Sprague Dawley rat; animal; animal behavior; decision making; dept.psy; male; peer-reviewed; physiology; pigeons and doves; probability; rat; reaction time; reinforcement; review; species difference

Exploring a concurrent-chains paradox: decreasing preference as an initial link is shortened. - Mazur, James E (Journal of experimental psychology. Animal behavior processes, 2005)
Experiments with pigeons and rats on concurrent-chains schedules examined a paradoxical effect reported by R. A. Preston and E. Fantino (1991). One schedule in the concurrent chain had a variable-interval (VI) 60-s initial link, and its terminal link was a 10-s delay to food. The other schedule had an initial link that ranged from VI 60 s to VI 2 s, and its terminal link was a 20-s delay to food. The paradoxical effect--a decrease in preference for the 20-s delay as its initial link was shortened--was found in some conditions but not in others. An analysis of response-reinforcer delays suggested that the paradoxical effect occurred in conditions in which responding on the short VI schedule almost always led to the 20-s delay, eliminating the possibility of switching to the alternative with the shorter delay. Copyright 2005 APA.
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Association Learning; Choice Behavior; Color Perception; Columba; Columbidae; Discrimination Learning; Models, Psychological; Motivation; Psychomotor Performance; Reaction Time; Reinforcement Schedule; animal; article; color vision; decision making; dept.psy; discrimination learning; learning; motivation; pigeons and doves; psychological model; psychomotor performance; reaction time; reinforcement

From Freud to Erikson to Marcia: Concept maps in personality psychology courses - Anthis, K (Teaching of Psychology, 2005)
This study examined concept maps produced by personality psychology students as a function of different types of concept map instruction. The results indicated the number of quantitative items in the students' concept maps significantly increased from the pretest to the posttest, as would be expected over the course of an academic semester. More importantly, the type of instructions the students received at the pretest played a significant role in the number of cross links depicted in the maps at the posttest. I discuss the results in term of the utility of instruction type when using concept maps in social science courses.
Keywords: dept.psy; ⛔ No DOI found

Heuristics and general principles of learning. - Mazur, James E (Behavioural Processes, 2005)
This research on decision-making heuristics is similar to research on animal learning in at least two ways. First, optimality modeling has not proven to be very useful for either research area. Second, both of these research areas seek to find general principles (or heuristics) that are applicable to different species in different settings. However, the basic principles of classical and operant conditioning seem to be more uniform across species and situations, whereas decision-making heuristics can vary for different species and different situations, even for tasks with very similar characteristics.
Keywords: *Algorithms; *Decision Making; *Learning; *Models, Psychological; Animalia; Animals; Decision-making; Heuristics; Humans; Optimality modeling; behavioral research; conditioned reflex; conference paper; decision making; dept.psy; heuristics; human; instrumental conditioning; learning; mental task; nonhuman

Varying initial-link and terminal-link durations in concurrent-chains schedules: a comparison of three models. - Mazur, James E (Behavioural Processes, 2004)
In Experiment 1, pigeons responded on concurrent-chains schedules with equal variable-interval schedules as initial links and fixed delays to food as terminal links. One terminal-link delay was always three times as long as the other. As terminal-link delays increased, response percentages on the key with the shorter terminal link increased according to a curvilinear function. This result supported the predictions of the hyperbolic value-added model and the contextual-choice theory but not delay-reduction theory. In Experiment 2, the terminal links were always delays of 2 s and 12 s, followed by food, and the durations of the initial links varied across conditions. As initial-link durations increased, pigeons' response percentages on the key with the shorter terminal link decreased, but toward an asymptote greater than 50%, indicating a continued preference for the shorter terminal link with very long initial links. This result was more consistent with the predictions of the hyperbolic-value added model than with those of the contextual-choice model or of delay-reduction theory. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: *Behavior, Animal; *Reinforcement, Psychology; Animals; Behavior, Animal; Columba; Columbidae; Concurrent-chains schedule; Initial links; Key peck; Pigeons; Reinforcement (Psychology); Terminal links; Time Factors; animal experiment; behavioral response; bird; conference paper; controlled study; decision making; dept.psy; experiment; food; intermethod comparison; model; modeling; nonhuman; pigeon; prediction; reinforcement; response time; temporal analysis; theory

Self-esteem, perception of relationships, and emotional distress: A cross-cultural study - Abe, Jo Ann A (Personal Relationships, 2004)
This study examined the relative importance of self-esteem, family cohesion, and support from friends in predicting depressed mood and anxiety in Japanese and American college students. Contrary to expectations, self-esteem was the strongest predictor of emotional distress in both groups of students. Nevertheless, consistent with predictions derived from Markus and Kitayama's theory of self-construals, family cohesion accounted for a significantly larger percentage of the variance in predicting emotional distress in Japan than in the United States. In both countries, the relations between support from friends and the measures of emotional distress were entirely mediated by self-esteem. However, among Japanese students, family cohesion accounted for additional significant variance in predicting the measures of emotional distress, even after controlling for self-esteem.
Keywords: dept.psy

Lexical influences in audiovisual speech perception - Brancazio, Lawrence (Journal of Experimental Psychology: Human Perception and Performance, 2004)
Phoneme identification with audiovisually discrepant stimuli is influenced by information in the visual signal (the McGurk effect). Additionally, lexical status affects identification of auditorily presented phonemes. The present study tested for lexical influences on the McGurk effect. Participants identified phonemes in audiovisually discrepant stimuli in which lexical status of the auditory component and of a visually influenced percept was independently varied. Visually influenced (McGurk) responses were more frequent when they formed a word and when the auditory signal was a nonword (Experiment 1). Lexical effects were larger for slow than for fast responses (Experiment 2), as with auditory speech, and were replicated with stimuli matched on physical properties (Experiment 3). These results are consistent with models in which lexical processing of speech is modality independent.
Keywords: *Lipreading; *Speech Perception; *Visual Perception; *Vocabulary; Adolescent; Adult; Female; Humans; Lipreading; Male; Phonetics; Reaction Time; Speech Perception; Visual Perception; Vocabulary; adolescent; adult; article; clinical trial; controlled clinical trial; controlled study; dept.psy; female; human; linguistics; lip reading; male; phonetics; randomized controlled trial; reaction time; speech perception; vision

Shame, guilt, and personality judgment - Abe, Jo Ann A (Journal of Research in Personality, 2004)
The purpose of this study was to shed further light on the intrapersonal and interpersonal correlates of shame- and guilt-proneness by examining their relations with self- and peer-ratings of the five-factor model (FFM) of personality. Shame- and guilt-proneness were assessed using a scenario-based and a checklist measure. Consistent with findings from previous research, the self-rating data yielded support for the view that shame-proneness may be associated with more maladaptive patterns than guilt-proneness. However, peer-ratings of personality failed to corroborate these findings. Both scenario-based and checklist measures of shame-proneness were associated with a tendency to underestimate one's Agreeableness relative to peer-ratings. Several possible interpretations of these findings are discussed in light of the extant research on personality judgment. (C) 2003 Elsevier Science (USA). All rights reserved.
Keywords: dept.psy; peer-reviewed

Gender and identity status differences in late adolescents’ possible selves - Anthis, Kristine; Dunkel, Curt S; Anderson, Brian (Journal of Adolescence, 2004)
The current study examined gender and identity status differences in late adolescents' possible selves. The intent of the study was to clarify conflicts between theory and research on gender differences in identity by investigating the content of participants' possible selves. Participants completed measures of identity and possible selves. The results indicated that there was a relationship between gender and the mean number of both feared and balanced interpersonally themed possible selves. The pattern of results is discussed in terms of prior findings regarding gender differences in both identity and possible selves. Suggestions for future research are also provided. (C) 2003 The Association for Professionals in Services for Adolescents. Published by Elsevier Ltd. All rights reserved.
Keywords: *Sex Factors; *Social Identification; Adolescent; Adult; Female; Humans; Male; Surveys and Questionnaires; United States; adolescent; adult; article; child behavior; controlled study; coping behavior; dept.psy; ego identity; ethnology; fear; female; gender identity; human; male; personality; race difference; sex difference; social status

Developmental changes in facial expressions of emotions in the strange situation during the second year of life - Izard, Carroll E; Abe, Jo Ann A (Emotion, 2004)
Infants' expressions of discrete emotions were coded during the more stressful episodes (4 through 8) of the Strange Situation at 13 and 18 months. The data showed a significant decrease in full-face expressions (more complex configurations of movements) and a significant increase in component expressions (simpler and more constrained patterns of movements). The authors interpreted this trend as a developmental change toward more regulated and less intense emotions. Consistent with this view, the aggregate index of infants' full-face negative emotion expressions, interpreted as reflecting relatively unregulated intense emotions, correlated significantly with maternal ratings of difficult temperament. The authors discuss alternative interpretations of the findings in terms of changes in reactivity/arousability and the emerging capacity for self-regulation.
Keywords: Adult; Affect; Arousal; Facial Expression; Female; Humans; Infant; Social Control, Informal; Temperament; adult; anger; arousal; article; body movement; body posture; child behavior; child development; child parent relation; dept.psy; emotion; face; facial expression; happiness; human; infant; longitudinal study; mother child relation; rating scale; temperament

Therapist variables that predict symptom change in psychotherapy with chronically depressed outpatients. - Vocisano, Carina; Klein, Daniel N; Arnow, Bruce A; Rivera, Caridad; Blalock, Janice A; Rothbaum, Barbara O; Vivian, Dina; Markowitz, John C; Kocsis, James H; Manber, Rachel; Castonguay, Louis G; Rush, A John; et al. (Psychotherapy, 2004)
The present study examines the contribution of psychotherapist variables to change in depressive symptoms in a large clinical trial comparing the efficacy of the cognitive-behavioral analysis system of psychotherapy, the antidepressant nefazodone, and the combination of both in the treatment of chronic depression. Greater change on the Hamilton Rating Scale for Depression (HRSD) was associated with greater emphasis on the therapeutic relationship, lower overall psychotherapy caseload, therapist psychodynamic orientation, and supervisory status. There was no relationship between HRSD change and therapist sex, age, or years of experience.
Keywords: Hamilton scale; adult; age; article; behavior therapy; clinical practice; clinical trial; cognitive therapy; controlled clinical trial; controlled study; depression; dept.psy; doctor patient relation; drug efficacy; female; gender; human; major clinical study; male; multicenter study; nefazodone; normal human; outpatient; patient care; patient guidance; physician attitude; prediction; psychodynamics; psychopharmacotherapy; psychotherapist; psychotherapy; randomized controlled trial; symptomatology; workload

Visual influences on the internal structure of phonetic categories - Brancazio, L; Miller, JL; Pare, MA (Perception & Psychophysics, 2003)
Previous work has demonstrated that the graded internal structure of phonetic categories is sensitive to a variety of contextual factors. One such factor is place of articulation: The best exemplars of voiceless stop consonants along auditory bilabial and velar voice onset time (VOT) continua occur over different ranges of VOT! (Volaitis & Miller, 1992). In the present study, we exploited the McGurk effect to examine whether-visual information for place of articulation also shifts the best-exemplar range for voiceless consonants, following Green and Kuhl's (1989) demonstration of effects of visual place of articulation on the location of voicing boundaries. In Experiment 1, we established that /p/ and /t/ have different best-exemplar ranges along auditory bilabial and alveolar VOT continua. We then found, in Experiment 2, a-similar shift in the best-exemplar range for /t/ relative to that for /p/ when there was a change in visual place of articulation, with auditory place of articulation held constant. These findings indicate-that the perceptual mechanisms that determine internal phonetic category structure-are sensitive to visual, as well as to Auditory, information.
Keywords: Adolescent; Adult; Female; Humans; Male; Middle Aged; Phonetics; Random Allocation; Speech Perception; Time Factors; Visual Perception; Voice; adolescent; adult; article; dept.psy; female; human; male; middle aged; phonetics; randomization; speech perception; time; vision; voice

Effects of free-food deliveries and delays on choice under concurrent-chains schedules. - Mazur, James E (Behavioural Processes, 2003)
Pigeons responded on a concurrent-chains schedule with two equal variable-interval (VI) schedules as initial links and delays to food of 3 and 12 s as the two terminal links. In even-numbered sessions, no other reinforcement schedule was present, and all pigeons showed a strong preference for the response key that had the shorter, 3-s terminal-link delay. In odd-numbered sessions, the initial links were interrupted at random times by one of three different types of events. When the interruptions were immediate food deliveries, the response percentages increased on the key that had the 3-s delay. When the interruptions were 30-s delays followed by food, the response percentages remained approximately unchanged. When the interruptions were 30-s delays with no food, the response percentages decreased. The results were used to compare the predictions of different mathematical models of concurrent-chains performance. The results favored models that assume that preference is determined by the relative amount of advantage that is gained when a terminal link is entered. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Choice; Columba; Concurrent chains; Free food; Key peck; Pigeons; Reinforcer delay; animal behavior; animal experiment; article; controlled study; decision making; dept.psy; food; food deprivation; mathematical model; nonhuman; pigeon; prediction; preference behavior; reinforcement; stimulus response

The role of sexist discrimination in adult women's identity development - Anthis, Kristine (Sex Roles, 2002)
The purpose of the current study was to examine the relationship between sexist discrimination and identity development in a sample of adult women. Participants completed a scale to indicate the extent to which sexist events had occurred in their lives and a measure of identity at 2 different data collection periods that spanned approximately 5 months. The results indicated that sexist events reported to occur within the last year at the first data collection period significantly predicted identity scores at the second data collection period. These findings are discussed in terms of how sexist discrimination may play a role in adult women's identity development and in terms of the additional psychometric data that supports the validity of the measure of sexist discrimination.
Keywords: dept.psy; identity; sexist discrimination; women

Winning friends and influencing peers: Strategies of peer influence in late childhood - Hawley, Patricia H; Little, Todd D; Pasupathi, Monisha (International Journal of Behavioral Development, 2002)
We divided children (N = 719, grades 3-6) into five control types based on the degree to which they reported employing prosocial (indirect, cooperative) and coercive (direct, hostile) strategies of control (prosocial controllers, coercive controllers, bistrategic controllers, noncontrollers, and typicals). We tested for differences across the five types on personal characteristics, friendship motivations, wellbeing, and social integration, expecting specific patterns according to whether control is wielded, and whether coercive or prosocial behaviour (or both) is employed. Prosocial controllers revealed positive characteristics (e. g., social skills, agreeableness), intrinsic friendship motivations, and positive wellbeing. In contrast, coercive controllers revealed negative characteristics (e. g., hostility), extrinsic friendship motivations, and ill-being. Bistrategic controllers, as expected, reported the highest control, and revealed characteristics associated with both prosocial and coercive orientations. Noncontrollers, in contrast, did not report having these characteristics and felt the least effective in the peer group. Our evolutionary perspective offers unique predictions of how prosocial and coercive children are similar in terms of their instrumental goals and the consequences of using both strategies or neither.
Keywords: childhood; controlled study; cooperation; dept.psy; female; hostility; human; male; motivation; perception; personality test; persuasive communication; prediction; review; school child; social adaptation; social control; social interaction; sociology; wellbeing

Evidence against a constant-difference effect in concurrent-chains schedules - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2002)
Savastano and Fantino (1996) reported that in concurrent-chains schedules, initial-link choice proportions remained constant as terminal-link durations increased as long as the subtractive difference between the two terminal-link schedules remained constant. Two experiments with pigeons were conducted to examine this constant-difference effect. Both experiments used equal variable-interval schedules as initial links. The terminal links were fixed delays to reinforcement in Experiment 1 and variable delays to reinforcement in Experiment 2. The durations of the terminal links were varied across conditions, but the difference between pairs of terminal links was always 10 s. In both experiments, preference for the shorter terminal link became less extreme as terminal-link, durations increased, so a constant-difference effect was not found, It is argued, however, that this choice situation does not provide clear evidence for or against delay-reduction theory versus other theories of choice.
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Choice Behavior; Color Perception; Columbidae; Concurrent-chains schedules; Delay-reduction theory; Fixed delays; Key peck; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Variable delays; animal; appetite; article; color vision; comparative study; decision making; dept.psy; motivation; peer-reviewed; pigeons and doves; recall; reinforcement

Social dominance and prosocial and coercive strategies of resource control in preschoolers - Hawley, P.H. (International Journal of Behavioral Development, 2002)
This study was designed to investigate the predictors of social dominance, the strategies children use to control resources (prosocial and coercive), and the associations between these strategies and measures of personality, social skills, and peer regard. A total of 30 preschoolers (ages 3-6) were rated by their teachers on social dominance. Based on these ratings, dominant children were paired with multiple subordinate children (i.e., block design; Kenny, 1990) and observed in a play situation designed to elicit resource control behaviour. As hypothesised, age and the surgency facet of extraversion predicted social dominance (but openness to experience did not). Furthermore, also as expected, both prosocial behaviour and coercive behaviour were related to resource control in the play situation. Last, both resource control strategies were associated with parent-rated social competence, but only coercive control was associated with positive peer regard (i.e., Likeability). Factors of personality (e.g. agreeableness, hostility) were not associated with either of the strategies. The utility of an evolutionary perspective to resource control and social competence is discussed.
Keywords: article; controlled study; dept.psy; female; group psychology; hostility; human; hypothesis; male; parent; personality; persuasive communication; play; prediction; preschool child; social adaptation; social behavior; social dominance; sociology; teacher

Concurrent-chain performance in transition: effects of terminal-link duration and individual reinforcers. - Mazur, James E (Animal learning & behavior, 2002)
Pigeons responded on concurrent-chain schedules with variable-interval initial links and equal delays as terminal links. The terminal-link delays were 1 sec in some conditions and 20 sec in other conditions. The percentages of reinforcers delivered for responses on the left key were 10%, 30%, 70%, or 90%, and this percentage was switched every five to nine sessions. The rate of change in the pigeons' response percentages after a switch was the same whether the terminal-link delays were 1 sec or 20 sec. Analysis of the effects of individual reinforcers showed that after a response on one key had been reinforced, response percentages on that key were higher for at least the next 100 responses. Small effects of individual reinforcers were evident after eight or nine additional reinforcers had been delivered. The effects of individual reinforcers were about equally large during times of transition and during periods in which overall response percentages were relatively stable.
Keywords: *Behavior, Animal; *Reinforcement, Psychology; Animalia; Animals; Columba; Columbidae; Random Allocation; Reaction Time; Reinforcement Schedule; animal experiment; article; conditioned reflex; conditioning; decision making; dept.psy; nonhuman; pigeon; reinforcement; task performance

Transitional choice behavior in concurrent-chain schedules - Mazur, James E; Blake, Nancy; Mcmanus, Courtney (Behavioural Processes, 2001)
The choice responses of four pigeons were examined in 20 periods of transition in a concurrent-chain procedure with variable-interval schedules as initial links and fixed delays to reinforcement as terminal links. In some conditions, the delays to reinforcement were different for the two terminal links, and changes in preference were recorded after the delays for the two response keys were switched. In other conditions, the reinforcer delays were equal for the two keys, but which key delivered 80% of the reinforcers was periodically switched. Choice proportions changed more quickly after a switch in reinforcement percentages chan after a switch in the delays, thereby contradicting the hypothesis that faster changes would occur when the switch in conditions was easier to discriminate. Analyses of response sequences showed that the effects: of individual reinforcers were larger and lasted longer in conditions with changing reinforcement percentages than in conditions with changing terminal-link delays. Rates of change in choice behavior do not appear to be limited by the unpredictability of variable reinforcement schedules, because the changes in behavior were slow and gradual even when there was a large and sudden change in reinforcer delays. (C) 2001 Elsevier Science B.V. All rights: reserved.
Keywords: Columba; Concurrent-chain schedules; Transitional choice behavior; animal experiment; article; behavior; controlled study; decision making; dept.psy; instrumental conditioning; nonhuman; pigeon; reinforcement; stimulus response

Hyperbolic value addition and general models of animal choice - Mazur, James E. (Psychological Review, 2001)
Three mathematical models of choice-the contextual-choice model (R. Grace, 1994), delay-reduction theory (N. Squires & E. Fantino, 1971). and a new model called the hyperbolic value-added model-were compared in their ability to predict the results from a wide variety of experiments with animal subjects. When supplied with 2 or 3 free parameters, all 3 models made fairly accurate predictions for a large set of experiments that used concurrent-chain procedures. One advantage of the hyperbolic value-added model is that it is derived from a simpler model that makes accurate predictions for many experiments using discrete-trial adjusting-delay procedures. Some results favor the hyperbolic value-added model and delay-reduction theory over the contextual-choice model, but more data are needed from choice situations For which the models make distinctly different predictions.
Keywords: *Behavior, Animal; *Choice Behavior; *Models, Psychological; Animals; Behavior, Animal; Choice Behavior; Columbidae; Conditioning (Psychology); Conditioning, Psychological; Models, Psychological; Reinforcement (Psychology); Reinforcement Schedule; Reinforcement, Psychology; animal; animal behavior; comparative study; conditioning; decision making; dept.psy; pigeons and doves; psychological model; reinforcement; review; ⚠️ Invalid DOI

Two- versus three-alternative concurrent-chain schedules: a test of three models. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2000)
Two experiments with pigeons used concurrent-chain procedures with variable-interval schedules as initial links and different delays to food as terminal links. Two schedules were present in all sessions. but a 3rd schedule was alternately present and absent in successive sessions. When the 3rd schedule delivered food with no terminal-link delay, the presence of this schedule led to an increase in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. When the terminal-link delay for the 3rd schedule was 30 s, the presence of this schedule led to a decrease in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. These results are inconsistent with the predictions of R. Grace's (1994) contextual-choice model, but they are consistent with 2 other mathematical models-delay-reduction theory and the hyperbolic value-added model.
Keywords: *Choice Behavior; *Columbidae; *Conditioning, Operant; Analysis of Variance; Animals; Choice Behavior; Columbidae; Conditioning, Operant; Models, Psychological; analysis of variance; animal; article; decision making; dept.psy; instrumental conditioning; pigeons and doves; psychological model

Tradeoffs among delay, rate, and amount of reinforcement - Mazur, James E (Behavioural Processes, 2000)
In Experiment I, an adjusting-delay procedure was used to measure pigeons' choices between a single delayed reinforcer and a range of different variable-time schedules. Indifference points showed an inverse relation between rate of reinforcement and delay that was well described by a hyperbolic equation. An adjusting-amount procedure was used in Experiment 2, in which pigeons chose between an adjusting amount of food delivered after a 0.5-s delay and 3 s of food delivered after a range of different delays, and the effects of delay were similar to those found in Experiment 1. The results from both experiments indicated that, for pigeons, the strength of a reinforcer decreased rapidly with increasing delay. Estimates of a decay rate parameter in the hyperbolic equation were similar to those found in other studies with pigeons, but the rates of temporal discounting were three or four times faster than those found in studies with rats, suggesting a possible species difference. (C) 2000 Published by Elsevier Science B.V. All rights reserved.
Keywords: Adjusting procedure; Amount of reinforcement; Delay; Discounting; Key peck; Pigeons; Rate of reinforcement; animal experiment; article; behavior; controlled study; dept.psy; dose time effect relation; nonhuman; pigeon; reinforcement; technique; variance

Early and chronic stress and their relation to breast cancer - Jacobs, John R; Bovasso, Gregory B (Psychological Medicine, 2000)
Background. The study examined the role of parental death and chronic depression with severe episodes in affecting risk of breast cancer. This avenue of research is in accord with oncology findings, which suggests that causative factors of breast cancer occur and develop over a period of 20 years or longer. Methods. Participants consisted of 1213 women in the Baltimore Epidemiologic Catchment Area study surveyed in 1980 and followed through 1994-1995. They were assessed for depressive and anxious disorders, paternal death in childhood and relatively recent adverse life events prior to cancer hospitalization. Results. In the course of the study, 29 women were hospitalized for breast cancer and 10 died of breast cancer. The psychosocial variables that predicted increased risk of breast cancer were maternal death in childhood (OR = 2.56, P ¡ 0.001) and chronic depression with severe episodes (OR = 14.0, P ¡ 0.001). Neither relatively recent life events nor other depressive and anxiety disorders were associated with increased risk. Maternal death and chronic depression with severe episodes were reported to have occurred at least 20 years prior to breast cancer hospitalization. Conclusions. Maternal death and chronic and severe depression occurred at least 20 years prior to breast cancer hospitalization and could have been involved in the causation or facilitation of cancer development. The authors suggest that meta-analysis of other prospective studies are needed to create larger groups of individuals with these stresses to confidently establish these variables as risk factors.
Keywords: *Breast Neoplasms/et [Etiology]; *Death; *Depressive Disorder/co [Complications]; *Stress, Psychological; Adult; Breast Neoplasms; Breast Neoplasms/px [Psychology]; Death; Depressive Disorder; Epidemiologic Studies; Female; Humans; Life Change Events; Middle Aged; Mother-Child Relations; Risk Factors; Stress, Psychological; adult; anxiety neurosis; article; breast cancer; cancer risk; depression; dept.psy; female; health survey; hospitalization; human; life event; major clinical study; medical psychology; mental stress; parental deprivation

Visual influences on perception of speech and nonspeech vocal-tract events. - Brancazio, Lawrence; Best, Catherine T; Fowler, Carol A (Language and speech, 2006)
We report four experiments designed to determine whether visual information affects judgments of acoustically-specified nonspeech events as well as speech events (the "McGurk effect"). Previous findings have shown only weak McGurk effects for nonspeech stimuli, whereas strong effects are found for consonants. We used click sounds that serve as consonants in some African languages, but that are perceived as nonspeech by American English listeners. We found a significant McGurk effect for clicks presented in isolation that was much smaller than that found for stop-consonant-vowel syllables. In subsequent experiments, we found strong McGurk effects, comparable to those found for English syllables, for click-vowel syllables, and weak effects, comparable to those found for isolated clicks, for excised release bursts of stop consonants presented in isolation. We interpret these findings as evidence that the potential contributions of speech-specific processes on the McGurk effect are limited, and discuss the results in relation to current explanations for the McGurk effect.
Keywords: *Illusions; *Speech Perception/ph [Physiology]; *Visual Perception/ph [Physiology]; Acoustic Stimulation; Attention; Audiovisual speech perception; Clicks; Humans; McGurk effect; Nonspeech; Perceptual Masking; Psychoacoustics; Speech Acoustics; dept.psy

Words that predict outstanding performance - Abe, Jo Ann A. (Journal of Research in Personality, 2009)
This study applied word count strategies developed by expressive writing researchers to examine whether the words students use to describe and reflect on their field practicum experiences would predict practicum supervisors' ratings of their performance. The weekly journals of 66 students who completed a practicum at a mental health or school setting were analyzed using a computerized text-analysis program. As expected, positive emotion words and "insight" words were positively correlated with almost all dimensions of evaluation, with the exception of organizational ability, and "we" words were associated with dimensions that focused on interpersonal relations. These findings further support the view that positive emotion words and "insight" words are powerful markers of cognitive broadening and behavioral flexibility and that "we" words index feelings of affiliation and belonging. As one might expect, there was an increase in "we" words and a decrease in "anxiety" words over the course of the internship. © 2009 Elsevier Inc. All rights reserved.
Keywords: Experiential learning; Positive emotions; Reflection; Text-analysis; dept.psy; peer-reviewed

Delay-amount tradeoffs in choices by pigeons and rats: hyperbolic versus exponential discounting. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2009)
An adjusting-delay procedure was used to study the choices of pigeons and rats when both delay and amount of reinforcement were varied. In different conditions, the choice alternatives included one versus two reinforcers, one versus three reinforcers, and three versus two reinforcers. The delay to one alternative (the standard alternative) was kept constant in a condition, and the delay to the other (the adjusting alternative) was increased or decreased many times a session so as to estimate an indifference point--a delay at which the two alternatives were chosen about equally often. Indifference functions were constructed by plotting the adjusting delay as a function of the standard delay for each pair of reinforcer amounts. The experiments were designed to test the prediction of a hyperbolic decay equation that the slopes of the indifference functions should increase as the ratio of the two reinforcer amounts increased. Consistent with the hyperbolic equation, the slopes of the indifference functions depended on the ratios of the two reinforcer amounts for both pigeons and rats. These results were not compatible with an exponential decay equation, which predicts slopes of 1 regardless of the reinforcer amounts. Combined with other data, these findings provide further evidence that delay discounting is well described by a hyperbolic equation for both species, but not by an exponential equation. Quantitative differences in the y-intercepts of the indifference functions from the two species suggested that the rate at which reinforcer strength decreases with increasing delay may be four or five times slower for rats than for pigeons.
Keywords: *Choice Behavior; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning, Operant; Long Evans rat; Male; Models, Psychological; Rats; Rats, Long-Evans; Reinforcement Schedule; Reward; animal; article; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; pigeons and doves; psychological model; rat; reinforcement; reward

Re-examining the long-term effects of experiencing parental death in childhood on adult psychopathology. - Jacobs, John R; Bovasso, Gregory B (Journal of Nervous and Mental Disease, 2009)
This study examined whether the experience of the death of a parent in childhood increases risk for adult psychopathology. Participants consisted of 3481 men and women gathered through the Baltimore Epidemiologic Catchment Area study in 1981 and followed through 1994-1995. The Diagnostic Interview Survey was administered by trained interviewers and was used to assess DSM-III disorders including major depression, panic, and anxiety disorders. Maternal death was not a predictor of adult psychopathology. The death of the father during childhood more than doubled the risk for major depressive disorder in adulthood. This study did not find any significant interactions between gender of the deceased parent and gender of the participant nor did the current age of the participant or their age at the time of the death of a parent affect risk for adult psychopathology. The long-term effect on adult depression of the experience of the death of the father in childhood is attributed to likely financial stresses, which may have continued for years and possibly into early adulthood, complicating the family's adaptation to the initial loss.
Keywords: *Bereavement; *Death; *Mental Disorders/et [Etiology]; *Mental Disorders/px [Psychology]; *Parents; *Psychology, Child; Anxiety Disorders; Anxiety Disorders/di [Diagnosis]; Anxiety Disorders/et [Etiology]; Anxiety Disorders/px [Psychology]; Bereavement; Child Psychology; Death; Depression; Depressive Disorder, Major; Depressive Disorder, Major/di [Diagnosis]; Depressive Disorder, Major/ep [Epidemiology]; Depressive Disorder, Major/et [Etiology]; Depressive Disorder, Major/px [Psychology]; Diagnostic and Statistical Manual of Mental Disorders; Economics; Fathers; Female; Humans; Incidence; Male; Mental Disorders; Middle Aged; Mothers; Panic; Parental death; Parents; Prevalence; Risk Factors; Stress, Psychological; Stress, Psychological/et [Etiology]; Time Factors; adaptive behavior; adult; adulthood; anxiety disorder; article; bereavement; child psychology; childhood; death; depression; dept.psy; diagnostic and statistical manual of mental disorders; economics; family stress; father; female; gender; human; incidence; interview; major depression; male; maternal mortality; mental disease; mental stress; middle aged; mother; normal human; panic; parent; parental deprivation; personal experience; prevalence; psychological aspect; risk factor; time; time of death

Training in assessment criteria indicative of deception to improve credibility judgments - Colwell, Kevin; Hiscock-Anisman, Cheryl; Memon, Amina; Colwell, Lori H.; Taylor, Laura; Woods, Debra (Journal of Forensic Psychology Practice, 2009)
The recent attention given to false confessions and convictions underscores the need for a valid and applicable system of credibility assessment. The current study demonstrates the effectiveness of assessment criteria indicative of deception (ACID) training in increasing rater's ability to discriminate between honest and deceptive transcripts. ACID generates credibility assessment through analysis of behaviors related to memory and impression-management as they occur during the course of an investigative interview. Raters were taught that honest responses are longer, more vivid, and more spontaneous than deceptive responses. Conversely, deceptive responses are shorter, less vivid, more rigid, more carefully phrased, and less likely to change during the course of an investigative interview. Trained raters were able to correctly identify 77% of transcripts as honest or deceptive, whereas untrained raters correctly identified 57%. Future research should focus on using the ACID technique in more realistic situations and should involve training of professional investigators.
Keywords: Credibility; Detecting deception; Investigative interviewing; accuracy; analytic method; article; assessment criteria indicative of deception; behavioral research; controlled study; criminal justice; decision making; dept.psy; honesty; human; interview; self evaluation; training

Does choice of college textbook make a difference in students' comprehension? - Durwin, Cheryl Cisero; Sherman, William M (College Teaching, 2008)
The authors investigate whether the choice of college textbook affects students' comprehension of the material. Forty-eight students from educational psychology courses were randomly assigned to one of two conditions: (1) unfamiliar passages drawn from the textbook used in the course, or (2) comparable passages selected from a competitor textbook. Students read three passages and completed comprehension tests and an opinion survey. No significant differences were found. Implications for textbook selection practices are presented in the discussion section. © 2008, Copyright Taylor & Francis Group, LLC.
Keywords: comprehension; dept.psy; student preferences; textbook selection

Effects of reinforcer delay and variability in a successive-encounters procedure. - Mazur, James E (Learning & behavior, 2008)
Pigeons responded in a successive-encounters procedure that consisted of a search period, a choice period, and a handling period. The search period was either a fixed-interval or a mixed-interval schedule presented on the center key of a three-key chamber. Upon completion of the search period, the center key was turned off and the two side keys were lit. A pigeon could either accept a delay followed by food (by pecking the right key) or reject this option and return to the search period (by pecking the left key). During the choice period, a red right key represented the long alternative (a long handling delay followed by food), and a green right key represented the short alternative (a short handling delay followed by food). The experiment consisted of a series of comparisons for which optimal diet theory predicted no changes in preference for the long alternative (because the overall rates of reinforcement were unchanged), whereas the hyperbolic-decay model predicted changes in preference (because the delays to the next possible reinforcer were varied). In all comparisons, the results supported the predictions of the hyperbolic-decay model, which states that the value of a reinforcer is inversely related to the delay between a choice response and reinforcer delivery.
Keywords: *Choice Behavior; *Reinforcement, Psychology; Animals; Behavior, Animal; Choice Behavior; Columbidae; Male; Reinforcement (Psychology); Time Factors; animal; animal behavior; animal experiment; article; conditioning; controlled study; decision making; dept.psy; food; male; nonhuman; pigeon; pigeons and doves; psychological theory; reinforcement; time

Rats’ choices between one and two delayed reinforcers - Mazur, James E (Learning & Behavior, 2007)
Rats chose between alternatives that differed in the number of reinforcers and in the delay to each reinforcer. A left leverpress led to two reinforcers, each delivered after a fixed delay. A right leverpress led to one reinforcer after an adjusting delay. The adjusting delay was increased or decreased many times in a session, depending on the rat's choices, in order to estimate an indifference point-a delay at which the two alternatives were chosen about equally often. Both the number of reinforcers and their individual delays affected the indifference points. The overall pattern of results was well described by the hyperbolic-decay model, which states that each additional reinforcer delivered by an alternative increases preference for that alternative but that a reinforcer's effect is inversely related to its delay. Two other possible delay-discounting equations, an exponential equation and a reciprocal equation, did not produce satisfactory predictions for these data. Adding an additional free parameter to the hyperbolic equation as an exponent for delay did not appreciably improve the predictions, suggesting that raising delay to some power other than 1.0 was unnecessary. The results were qualitatively similar to those from a previous experiment with pigeons (Mazur, 1986), but quantitative differences suggested that the rates of delay discounting were several times slower for rats than for pigeons.
Keywords: *Choice Behavior; *Conditioning, Operant; *Motivation; *Reinforcement Schedule; *Time Perception; Animals; Male; Models, Theoretical; Rats; Rats, Sprague-Dawley; animal behavior; animal experiment; article; conditioning; dept.psy; hyperbolic decay model; mathematical model; nonhuman; pigeon; predictive validity; rat; reinforcement

Species differences between rats and pigeons in choices with probabilistic and delayed reinforcers - Mazur, James E. (Behavioural Processes, 2007)
An adjusting-delay procedure was used to study rats' choices with probabilistic and delayed reinforcers, and to compare them with previous results from pigeons. A left lever press led to a 5-s delay signaled by a light and a tone, followed by a food pellet on 50% of the trials. A right lever press led to an adjusting delay signaled by a light followed by a food pellet on 100% of the trials. In some conditions, the light and tone for the probabilistic reinforcer were present only on trials that delivered food. In other conditions, the light and tone were present on all trials that the left lever was chosen. Similar studies with pigeons [Mazur, J.E., 1989. Theories of probabilistic reinforcement. J. Exp. Anal. Behav. 51, 87-99; Mazur, J.E., 1991. Conditioned reinforcement and choice with delayed and uncertain primary reinforcers. J. Exp. Anal. Behav. 63, 139-150] found that choice of the probabilistic reinforcer increased dramatically when the delay-interval stimuli were omitted on no-food trials, but this study found no such effect with the rats. In other conditions, the probability of food was varied, and comparisons to previous studies with pigeons indicated that rats showed greater sensitivity to decreasing reinforcer probabilities. The results support the hypothesis that rats' choices in these situations depend on the total time between a choice response and a reinforcer, whereas pigeons' choices are strongly influenced by the presence of delay-interval stimuli. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: *Association Learning/ph [Physiology]; *Choice Behavior/ph [Physiology]; *Probability Learning; *Reinforcement, Psychology; *Time Perception/ph [Physiology]; Animals; Columba; Columbidae; Delay-interval stimuli; Delayed reinforcers; Probabilistic reinforcers; Rats; Rats, Sprague-Dawley; Rattus; Species Specificity; Time Factors; animal experiment; article; behavioral response; controlled study; decision making; dept.psy; food; food intake; gamebird; nonhuman; probability; rat; reinforcement; rodent; species difference; stimulus

Choice in a successive-encounters procedure and hyperbolic decay of reinforcement. - Mazur, James E (Journal of the experimental analysis of behavior, 2007)
Pigeons responded in a successive-encounters procedure that consisted of a search state, a choice state, and a handling state. The search state was either a fixed-interval or mixed-interval schedule presented on the center key of a three-key chamber. Upon completion of the search state, the choice state was presented, in which the center key was off and the two side keys were lit. A pigeon could either accept a delay followed by food (by pecking the right key) or reject this option and return to the search state (by pecking the left key). During the choice state, a red right key represented the long alternative (a long handling delay followed by food), and a green right key represented the short alternative (a short handling delay followed by food). In some conditions, both the short and long alternatives were fixed-time schedules, and in other conditions both were mixed-time schedules. Contrary to the predictions of both optimal foraging theory and delay-reduction theory, the percentage of trials on which pigeons accepted the long alternative depended on whether the search and handling schedules were fixed or mixed. They were more likely to accept the long alternative when the search states were fixed-interval rather than mixed-interval schedules, and more likely to reject the long alternative when the handling states were fixed-time rather than mixed-time schedules. This pattern of results was in qualitative agreement with the predictions of the hyperbolic-decay model, which states that the value of a reinforcer is inversely related to the delay between a choice response and reinforcer delivery.
Keywords: *Choice Behavior; *Reinforcement, Psychology; Animals; Choice; Choice Behavior; Columbidae; Delay-reduction theory; Hyperbolic-decay model; Key peck; Male; Optimal foraging theory; Pigeons; Reinforcement (Psychology); Successive-encounters procedure; animal; article; decision making; dept.psy; male; peer-reviewed; pigeons and doves; reinforcement

Mathematical models and the experimental analysis of behaviour - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2006)
The rise of mathematical models in the experimental analysis of behavior has increased over the years, and they offer several advantages. Mathematical models require theorists to be precise and unambiguous, often allowing comparisons of competing theories that sound similar when stated in words. Sometimes different mathematical models may make equally accurate predictions for a large body of data. In Such cases, it is important to find and investigate situations for which the competing models make different predictions because, unless two models are actually mathematically equivalent, they are based on different assumptions about the psychological processes that underlie ail observed behavior. Mathematical models developed in basic behavioral research have been used to predict and control behavior in applied settings, and they have guided research in other areas of psychology. A good mathematical model call provide a common framework for understanding what might otherwise appear to be diverse and unrelated behavioral phenomena. Because psychologists vary in their quantitative skills and in their tolerance for mathematical equations, it is important for those who develop mathematical models of behavior to find ways (such as verbal analogies, pictorial representations, or concrete examples) to communicate the key premises of their models to nonspecialists.
Keywords: *Models, Theoretical; *Social Behavior; Behavior; Equations; Humans; Mathematical models; Models, Theoretical; Reinforcement; Reinforcement (Psychology); Reinforcement, Psychology; Social Behavior; article; dept.psy; human; peer-reviewed; reinforcement; social behavior; theoretical model

Directed forgetting of a single item - Gottlob, Lawrence R; Golding, Jonathan M; Hauselt, William J (Journal of General Psychology, 2006)
In two experiments, we investigated directed forgetting of a single item. We presented participants with two phone numbers to remember and instructed half of the participants to forget the first phone number. The first number was either learned on a single trial (Experiment 1) or on three trials (Experiment 2). In Experiment 1, there was evidence of directed forgetting as a result of differential encoding; the forget instruction affected recall and recognition for both phone numbers. In Experiment 2, the evidence favored differential rehearsal because the forget instruction affected recall but not recognition. These results indicate that instructions to forget can affect memory of single items.
Keywords: Cues; Directed forgetting; Forgetting; Humans; Intentional forgetting; Memory; Mental Recall; Recall; Recognition (Psychology); Retention (Psychology); article; association; dept.psy; human; long term memory; recall; recognition

Readiness to change: A longitudinal study of changes in adult identity - Anthis, Kristine; Lavoie, Joseph C (Journal of Research in Personality, 2006)
It has been suggested in the identity literature that a readiness to change may play a role in identity development beyond adolescence, but an empirical investigation of this relationship had yet to be conducted until now. Therefore, the purpose of the current study was to establish a longitudinal relationship between readiness to change and adult identity development. Participants completed measures of readiness to change and identity at both the beginning and the end of the study. The results revealed a relationship between readiness to change and changes in identity exploration over the study interval, and between readiness to change and changes in identity commitment. The findings are discussed in terms of the currently available literature on identity development in adulthood. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Adults; Development; Identity; Stages of change; dept.psy; peer-reviewed

Does reflective journal writing improve course performance - Cisero, Cheryl A (College Teaching, 2006)
Abstract. This study investigated whether a reflective journal writing assignment would improve students' course performance. A total of 166 students from undergraduate sections of a course taught by the same instructor over three semesters completed the assignment as part of their requirements. Students (N = 317) from five previous semesters of the same course taught by the same instructor, who were not required to complete the assignment, served as a comparison group. Intervention and comparison groups were comparable on a variety of variables including all assignments, excepting the journal assignment. The findings are interpreted within the context of factors such as students' study habits and motivation. © 2006, Copyright Taylor & Francis Group, LLC.
Keywords: course performance; dept.psy; journal writing; motivation

Choice between single and multiple reinforcers in concurrent-chains schedules. - Mazur, James E (Journal of the experimental analysis of behavior, 2006)
Pigeons responded on concurrent-chains schedules with equal variable-interval schedules as initial links. One terminal link delivered a single reinforcer after a fixed delay, and the other terminal link delivered either three or five reinforcers, each preceded by a fixed delay. Some conditions included a postreinforcer delay after the single reinforcer to equate the total durations of the two terminal links, but other conditions did not include such a postreinforcer delay. With short initial links, preference for the single-reinforcer alternative decreased when a postreinforcer delay was present, but with long initial links, the postreinforcer delays had no significant effect on preference. In conditions with a postreinforcer delay, preference for the single-reinforcer alternative frequently switched from above 50% to below 50% as the initial links were lengthened. This pattern of results was consistent with delay-reduction theory (Squires & Fantino, 1971), but not with the contextual-choice model (Grace, 1994) or the hyperbolic value-added model (Mazur, 2001) as they have usually been applied. However, the hyperbolic value-added model could account for the results if its calculations were expanded to include reinforcers delivered in later terminal links. The implications of these findings for models of concurrent-chains performance are discussed.
Keywords: *Appetitive Behavior; *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Association Learning; Choice Behavior; Columbidae; Concurrent chains; Contextual-choice model; Delay-reduction theory; Discrimination Learning; Hyperbolic value-added model; Key peck; Motivation; Multiple reinforcers; Pigeons; Psychomotor Performance; Reinforcement Schedule; animal; appetite; article; decision making; dept.psy; discrimination learning; learning; motivation; peer-reviewed; pigeons and doves; psychomotor performance; reinforcement